Effects of Transportation on Racial/Ethnic Diversity of National Park Visitors. (4th March 2017) - Xiao, Xiao; Perry, Elizabeth; Manning, Robert; Krymkowski, Daniel; Valliere, William; Reigner, Nathan
ABSTRACT: The demographic composition of the United States is increasingly diverse, but racial/ethnic minority groups are substantially underrepresented in visiting national parks. Transportation is needed to provide access to national parks but may not be equally accessible to all groups in society. This study uses a general population survey of New York City residents to examine the role of transportation in visiting national parks by three racial/ethnic groups (Hispanic, Black, and White). Principle study variables were perceived barriers to visiting national parks and the importance of transportation-related incentives in encouraging visits to national parks. Study results identified three categories of barriers: comfort and safety, expense, and accessibility; Hispanics perceive higher levels of barriers than do Whites and Blacks. Transportation incentives may increase national park visitation, especially by Hispanics. Survey findings partially support the marginality and discrimination hypotheses, and suggest potentially effective strategies to increase park visitation by minority racial/ethnic groups.